2010
DOI: 10.1128/ec.00366-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Roco Protein Family in Dictyostelium discoideum

Abstract: The Roco family consists of multidomain Ras-GTPases that include LRRK2, a protein mutated in familial Parkinson's disease. The genome of the cellular slime mold Dictyostelium discoideum encodes 11 Roco proteins. To study the functions of these proteins, we systematically knocked out the roco genes. Previously described functions for GbpC, Pats1, and QkgA (Roco1 to Roco3) were confirmed, while novel developmental defects were identified in roco4-and roco11-null cells. Cells lacking Roco11 form larger fruiting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 28 publications
2
59
2
Order By: Relevance
“…Dictyostelium cells with a disruption in the roco4 gene cannot synthesize cellulose, resulting in instable stalks that are unable to lift the spore head ( Fig. 1C) (20). This strong developmental defect of roco4-nulls cells can be rescued completely by the expression of wild-type Roco4 and also by a chimeric protein of Roco4 in which the kinase domain is replaced by that of LRRK2 (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Dictyostelium cells with a disruption in the roco4 gene cannot synthesize cellulose, resulting in instable stalks that are unable to lift the spore head ( Fig. 1C) (20). This strong developmental defect of roco4-nulls cells can be rescued completely by the expression of wild-type Roco4 and also by a chimeric protein of Roco4 in which the kinase domain is replaced by that of LRRK2 (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Remarkably, the social amoeba Dictyostelium contains 11 Roco family members that contain a large variety of domains and have been studied in detail (19)(20)(21). In this study we used Dictyostelium Roco4, which has the same domain topology as LRRK2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, based on the LRRK2 primary protein sequence, the LRR domain is directly coupled to both the C terminus of the ankyrin domain and the N terminus of the Roc G-domain. Although mechanistically not well understood, recent studies did show that the N terminus of human LRRK2 and related Roco proteins is essential for function in vivo (45). Our data suggest that the LRRK2 ankyrin-LRR domains may play a direct role in the regulation of the LRRK2 kinase activity, guiding future in-depth functional characterization of LRRK2 at a molecular level.…”
Section: Discussionmentioning
confidence: 91%
“…12,22 Subsequent studies revealed a rich topology of domains that led to the classification of GbpC as a member of the Roco family of proteins. 23 A multi-step intramolecular activation mechanism has been identified for this protein 24,25 and its subcellular localization in response to cAMP-stimuli and osmotic shock was studied. 26 Despite our detailed mechanistic knowledge of GbpC activation, many open questions remain.…”
Section: Introductionmentioning
confidence: 99%